Prenatal Diagnosis of Congenital High Airway Obstruction Syndrome: Report of Two Cases and Brief Review of the Literature - Burcu Artunc Ulkumen; Halil Gursoy Pala; Nalan Nese; Serdar Tarhan; Yesim Baytur (Hindawi Limited, 2013)
Congenital high airway obstruction syndrome (CHAOS) is the obstruction of the fetal upper airways, which may be partial or complete. It is usually incompatible with life. Prenatal recognition of the disease is quite important due to the recently described management options. We report here two cases of CHAOS due to tracheal atresia diagnosed by antenatal ultrasonography and fetal MRI. We also briefly review the relevant literature with the associated management options.